EFEKTIVITAS IMPLEMENTASI MODEL DISCOVERY LEARNING DALAM PEMBELAJARAN AKIDAH AKHLAK KELAS XI MAN 2 MALANG - Atiyyatul Himmah, Lutfa; Busthomi, Yazidul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of the Discovery Learning model in the Aqidah Akhlak subject for eleventh-grade students at MAN 2 Malang. The research was motivated by the classroom learning practices that remain predominantly teacher-centered through the lecture method, resulting in limited student engagement and a superficial understanding of the learning materials. Employing a descriptive qualitative approach, the study collected data through classroom observations, in-depth interviews, and document analysis. The findings reveal that the implementation of the Discovery Learning model followed a systematic sequence consisting of stimulation, problem identification, data collection, data processing, verification, and conclusion drawing. The application of this model produced positive outcomes, as reflected in increased student participation, greater confidence in expressing opinions, enhanced critical thinking skills, and improved collaboration among students. Furthermore, students demonstrated a deeper understanding of the subject matter and were better able to internalize and apply the values of Aqidah Akhlak in their daily lives. The successful implementation of the model was supported by teachers' instructional readiness, students' high learning motivation, and a conducive school environment. However, several challenges remained, including limited instructional media and occasional classroom management issues. Therefore, the Discovery Learning model can be regarded as an effective instructional strategy for improving the quality of Aqidah Akhlak learning while strengthening students' religious character.